PEMISAHAN BERKAS PERKARA (SPLITSING) OLEH PENUNTUT UMUM DALAM PROSES PEMBUKTIAN SUATU TINDAK PIDANA PADA DELIK PENYERTAAN - Wisnu Waskitara (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTCriminal justice system is a term that indicates a working mechanism in crime prevention by using a basic system approach. All forms of participation or involvement of people both physically and psychologically in each act so that it gives birth to a criminal act is called participation (Deelneming). The separation of case files (splitsing) by the Public Prosecutor is one of the actions in law enforcement. Splitsing is carried out so that the elements of the offense from each defendant are fulfilled and in an effort to avoid a shortage of witness evidence.The purpose of writing is to find out the basis for the consideration of the Public Prosecutor in separating case files (splitsing) in a criminal case and knowing how to prove from a case file using the splitting method of case files (splitsing) in the inclusion offense. The type of research method used is empirical juridical using a sociological approach. Data collection techniques using interview techniques and data obtained from the research location using qualitative descriptive analysis techniques to answer the problems.The results of the research and discussion concluded that the Public Prosecutor in splitting the case files (splitsing) in a criminal case is to prove the guilt of the defendant in the trial, in criminal cases there is a shortage of witnesses, the status between the defendants is different, there are defendants who are still underage, cases that are offenses participation (deelneming), and in cases where some of the perpetrators have not been caught. Meanwhile, the method of proof from a case file using the splitting method for the inclusion offense is in the testimony of witnesses in which the defendant is used as a witness for other defendants, due to the lack of witness evidence in the case of participation crimes (deelneming). The trial process used remains the same as for ordinary criminal cases in general.